The Role of Training in Children's Art School in Fostering Psychological Wellbeing - Zotova, Olga; Tarasova, Lyudmila (Journal of Psychology and Psychotherapy Research, 2022)
The study addresses psychological features underlying healthy functioning of the individual and his/her successful management of stressful and tense situations. To study the role of training in children’s art school (CAS) in the formation of the given psychological features the authors conducted a comparative analysis of persons with full-time course of education in CAS and persons without such experience. The sample consisting of 257 participants was divided into three groups of comparison. The measures used in the study included the Ryff Scales of Psychological Wellbeing (adapted by T. D. Shevelkova and T. P. Fesenko), Maddi’s Hardiness Survey (modified by E. N. Osin and E. I. Rasskazova), and a questionnaire. The data were processed with the help of Kruskal–Wallis test, Mann–Whitney U test, and SPSS 20.0. The results have shown that the respondents with full-time training in CAS have higher indicators of psychological wellbeing and resilience. They are more aware of their value, integrity and meaningfulness of being, and have a more pronounced resource for coping with difficult, stressful situations. All these characteristics reflect the realm of experiences and states inherent in a healthy individual who is successful in his or her realization. The findings have revealed that even an incomplete course of studying in CAS creates the conditions for shaping personality wellbeing and resilience – features necessary for the person to combat stress and tension and function efficiently.